2014
DOI: 10.12998/wjcc.v2.i8.391
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in double cecal appendix: Case report

Abstract: male, white, 36 years old, obese, presenting with pain in the lower abdomen for 24 h followed by nausea, vomiting and mild fever. He was subjected to additional tests, with the leukogram showing leukocytosis and abdominal ultrasonography depicting cecal appendix with thickened wall, locally associated with small quantities of liquid and intestinal loop obstruction. He underwent laparotomy, revealing acute appendicitis. Another intestinal loop obstruction was identified next to the ileum, leading to recognizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…In two cases, the appendix was gangrenous 23,28 ( Table 2). The study by Alves et al 17 reported inflammation in both appendices, while Bulut et al 6 observed inflammation of the cecal region. This review also retrieved the first records of cases of Type A appendix duplication with removal of 35.56 cm of necrotic intestine 32 and another case of appendix duplication associated with diverticulitis in the Meckel's diverticulum, suggesting complete exploration of the cecum.…”
Section: Duplication Of Vermiform Appendixmentioning
confidence: 97%
See 2 more Smart Citations
“…In two cases, the appendix was gangrenous 23,28 ( Table 2). The study by Alves et al 17 reported inflammation in both appendices, while Bulut et al 6 observed inflammation of the cecal region. This review also retrieved the first records of cases of Type A appendix duplication with removal of 35.56 cm of necrotic intestine 32 and another case of appendix duplication associated with diverticulitis in the Meckel's diverticulum, suggesting complete exploration of the cecum.…”
Section: Duplication Of Vermiform Appendixmentioning
confidence: 97%
“…González et al 32 Female 7 A Volvulus of the appendix Necrosis of the intestine. Alves et al 17 Male 36 B Both appendices were swollen. Nazir et al 22 Female 33 B2 Only one inflamed appendix.…”
Section: Anatomical Variations Of the Vermiform Appendix And The Mesomentioning
confidence: 99%
See 1 more Smart Citation
“…Esto representa claramente un reto pues, por su rareza, en la práctica médica no se suele buscar; además, porque los estudios de imaginología para el dolor abdominal tienen poca sensibilidad para detectar estas malformaciones, y se han reportado pocos casos diagnosticados mediante tomografía o ecografía 19 . La importancia de un mal diagnóstico radica en que un segundo apéndice no resecado puede acarrear consecuencias clínicas y médico-legales graves, debido al alto riesgo de perforación y necesidad de reintervención, lo cual aumenta la morbimortalidad en estos pacientes 11,20 .…”
Section: Discussionunclassified
“…En general, es más comúnmente diagnosticada en adultos asintomáticos, como un hallazgo incidental durante el acto quirúrgico por otras causas o en estudios imaginológicos, como el presentado por Mahmood, et al, de una bifurcación apendicular detectada por tomografía y el de Peddu, et al, quienes detectaron una duplicación apendicular mediante un enema de bario [8][9][10] . Sin embargo, también se ha descrito en niños, generalmente asociada con otras malformaciones, como las intestinales o genitourinarias 11 .…”
Section: Introductionunclassified